The graphene oxide membrane immersing in the aqueous solution studied by electrochemical impedance spectroscopy. (27th April 2018) - Zhang, Yongjing; Chen, Zhe; Yao, Lei; Wang, Xiao; Fu, Ping; Lin, Zhidong
Abstract: The interlayer spacing of graphene oxide (GO) is a key property for GO membrane. To probe the variation of interlayer spacing of the GO membrane immersing in KCl aqueous solution, electrochemical impedance spectroscopy (EIS), x-ray diffraction (XRD) and computational calculation was utilized in this study. The XRD patterns show that soaking in KCl aqueous solution leads to an increase of interlayer spacing of GO membrane. And the EIS results indicate that during the immersing process, the charge transfer resistance of GO membrane decreases first and then increases. Computational calculation confirms that intercalated water molecules can result in an increase of interlayer spacing of GO membrane, while the permeation of K + ions would lead to a decrease of interlayer spacing. All the results are in agreement with each other. It suggests that during the immersing process, the interlayer spacing of GO enlarges first and then decreases. EIS can be a promisingly online method for examining the interlayer spacing of GO in the aqueous solution.